u=(arccosx)^n => du=n(arccosx)^(n-1)*(-1/sqrt(1-x^2))dx
dv=dx => v=x
I_n = x(arccosx)^n - int x*n(arccosx)^(n-1)*(-1/sqrt(1-x^2))dx
I_n = x(arccosx)^n + nint (arccosx)^(n-1)*x/sqrt(1-x^2)dx
u=(arccosx)^(n-1) => du=(n-1)(arccosx)^(n-2)*(-1/sqrt(1-x^2))dx
dv = x/sqrt(1-x^2)dx
v = int x/sqrt(1-x^2)dx
1-x^2=t => -2xdx=dt => xdx = -dt/2
v = -1/2int dt/sqrtt = -1/2 t^(1/2)/(1/2) = -sqrtt = -sqrt(1-x^2)
I_n = x(arccosx)^n + n[-(arccosx)^(n-1)sqrt(1-x^2) - int ( -sqrt(1-x^2))(n-1)(arccosx)^(n-2)*(-1/sqrt(1-x^2))dx]
I_n = x(arccosx)^n + n[-(arccosx)^(n-1)sqrt(1-x^2) - (n-1) int (arccosx)^(n-2)dx]
I_n = x(arccosx)^n - n(arccosx)^(n-1)sqrt(1-x^2) - n(n-1)I_(n-2)
We have recurrent formula, we only have to find I_1 and I_2 and that's trivial using Integration By Parts.